2013
DOI: 10.1111/bjh.12409
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of monocyte count at presentation in mantle cell lymphoma

Abstract: Summary An increased number of circulating monocytes at presentation has recently been associated with shorter survival in Hodgkin lymphoma, follicular lymphoma and diffuse large B cell lymphoma. This study aimed to assess the prognostic impact of the absolute monocyte count (AMC) at diagnosis in mantle cell lymphoma (MCL). AMC at diagnosis was available in 97 MCL cases recorded in the databases of the Oncology Institute of Southern Switzerland in Bellinzona (Switzerland) and the Division of Haematology of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 55 publications
4
34
2
Order By: Relevance
“…Although that analysis was based on a very small number of patients (27 were available for serum B2M), there was a huge difference reported in long‐term survival, with a 5‐year OS rate of 100% in patients with serum B2M ≤3 mg/L vs 22% in those with serum B2M >3 mg/L . In a previous study aimed to assess the prognostic impact of AMC for patients with MCL, serum B2M was also an independent prognostic factor .…”
Section: Discussionmentioning
confidence: 99%
“…Although that analysis was based on a very small number of patients (27 were available for serum B2M), there was a huge difference reported in long‐term survival, with a 5‐year OS rate of 100% in patients with serum B2M ≤3 mg/L vs 22% in those with serum B2M >3 mg/L . In a previous study aimed to assess the prognostic impact of AMC for patients with MCL, serum B2M was also an independent prognostic factor .…”
Section: Discussionmentioning
confidence: 99%
“…Virtually every other histotype of B-cell NHL and Hodgkin disease has now been shown to have significant macrophage component interactions that often show clinical significance [24]. More recent studies have shown that a high monocyte count at presentation in MCL can predict poor clinical outcomes [25,26]. The postulated mechanism for this relationship is that high monocyte count is a surrogate biomarker of the tumor microenvironment, reflecting the recruited peripheral blood immunosuppressive monocytes by the tumor transforming into tumor-associated macrophages, leading to cancer progression.…”
Section: Discussionmentioning
confidence: 99%
“…Absolute lymphocyte count was proven to be an independent prognostic factor in bladder cancer, melanoma and extranodal natural killer/T-cell lymphoma 8-10. Elevated monocyte count has been demonstrated to predict poor prognosis in mantle cell lymphoma, colorectal cancer and lung adenocarcinoma 11-13. Lymphocyte-to-monocyte ratio (LMR) has been shown to be a prognostic factor for patients with hepatocellular carcinoma and endometrial cancer 14, 15.…”
Section: Introductionmentioning
confidence: 99%